Increasing Adolescents' Knowledge of Family Preparation Through the Use of Audio-Visual Media - Erika Yulita Ichwan (GoAcademica Research & Publishing, 2023)
The high number of marriages and divorces in Indonesia, particularly in the DKI Jakarta area, is caused by the lack of readiness to marry both physically, mentally, and socially to be together in carrying out all of the family's obligations. The purpose of this research is to find out the comparison of knowledge and effectiveness between the use of audio-visual media and lectures on the level of knowledge of young adults about family preparation. This research uses the quasi-experimental method with a cross-sectional design. The population of this study is